(untitled) - White, John Stephen (Totowa, N.J., 2002)
Proteins, Pep tides and Amino Acids SourceBook is the second in a series of reference books conceived to cover the explosive growth in commercially available biological reagents. The success of our first reference work, Source Book of Enzymes published in 1997, encouraged us to continue this series. Choosing proteins, peptides, and amino acids as the subject matter for the second volume was simple, given their preeminence in regulating biochemical processes and their importance to modern molecular biology.
Keywords: Proteins,Proteins